Pre-pandemic mental and physical health as predictors of COVID-19 vaccine hesitancy: evidence from a UK-wide cohort study - G. David Batty; Ian J. Deary; Drew Altschul (Annals of Medicine, 2022)
Background Although several predictors of COVID-19 vaccine hesitancy have been identified, the role of physical health and, particularly, mental health, is poorly understood. Methods We used individual-level data from a pandemic-focused investigation (COVID Survey), a prospective cohort study nested within the UK Understanding Society (Main Survey) project. In the week immediately following the announcement of successful testing of the first efficacious inoculation (Oxford University/AstraZeneca, November/December 2020), data on vaccine intentionality were collected in 12,035 individuals aged 16–95 years. Pre-pandemic, study members had responded to enquiries about diagnoses of mental and physical health, including the completion of the 12-item General Health Questionnaire for symptoms of psychological distress (anxiety and depression). Peri-pandemic, individuals indicated whether they or someone in their household was shielding; that is, people judged by the UK National Health Service as being particularly clinically vulnerable who were therefore requested to remain at home. Intention to take up vaccination for COVID-19 was also self-reported. Results In an analytical sample of 11,955 people (6741 women), 15.4% indicated that they were vaccine-hesitant. Relative to their disease-free counterparts, shielding was associated with a 24% lower risk of being hesitant (odds ratio; 95% confidence interval: 0.76; 0.59, 0.96), after adjustment for a range of covariates which included age, education, and ethnicity. Corresponding results for cardiometabolic disease were 22% (0.78; 0.64, 0.95), and for respiratory disease were 26% (0.74; 0.59, 0.93). Having a pre-pandemic diagnosis of anxiety or depression, or a high score on the distress symptom scale, were all unrelated to the willingness to vaccine-hesitancy. Conclusions People with a physical condition were more likely to take up the potential offer of a COVID-19 vaccination. These effects were not apparent for indices of mental health.Key messages In understanding predictors of COVID-19 vaccine hesitancy, the role of physical and mental health has not been well-examined despite both groups seemingly experiencing an elevated risk of the disease. In a large UK cohort study, people with a pre-pandemic physical condition were more likely to take up the theoretical offer of vaccination. There were no apparent effects for indices of pre-pandemic mental health.